Development of a duplex droplet digital PCR assay for the detection of Burkholderia cepacia complex and Stenotrophomonas maltophilia in bloodstream infections - Chunmei Liu; Ziqiang He; Mimi Kong; Dong Jin (Microbiology Spectrum, 2024)
ABSTRACTBurkholderia cepacia complex (BCC) and Stenotrophomonas maltophilia are nosocomial pathogens that cause various infections and exhibit high resistance to multiple antimicrobial agents. In this study, we aimed to develop a duplex droplet digital PCR (ddPCR) assay for detecting BCC and S. maltophilia in bloodstream infections. We optimized the experimental conditions by setting the annealing temperature to 51°C and determining the optimal concentrations of primers and probes, as well as the thermal cycle numbers. The feasibility of the duplex ddPCR reaction system with the optimal conditions was established and verified through parallel reactions with reference strains of BCC and S. maltophilia. The specificity of the assay, tested with 33 reference strains, was found to be 100%. The duplex ddPCR assay demonstrated good repeatability and could detect as low as 5.35 copies/reaction of BCC and 7.67 copies/reaction of S. maltophilia. This level of sensitivity was consistent in the simulated blood and blood bottle samples. We compared nucleic acid extraction methods and found that the Chelex-100 boiling method and kit extraction method exhibited similar detection sensitivity, suggesting the potential application of the Chelex-100 boiling method in the ddPCR assay. In the clinical samples, the duplex ddPCR assay accurately detected BCC and S. maltophilia in 58 cases. In conclusion, our study successfully developed a duplex ddPCR assay that provides accurate and convenient detection of BCC and S. maltophilia in bloodstream infections.IMPORTANCEBurkholderia cepacia complex (BCC) and Stenotrophomonas maltophilia are implicated in a wide range of infections, including bloodstream infections (BSIs), pneumonia, and meningitis, and often exhibit high intrinsic resistance to multiple antimicrobial agents, limiting therapeutic options. The gold standard for diagnosing bloodstream infections remains blood culture. However, current blood culture detection and positivity rates do not meet the “rapid diagnosis” required for the diagnosis and treatment of critically ill patients with BSIs. The digital droplet PCR (ddPCR) method is a potentially more powerful tool in the diagnosis of BSIs compared to other molecular methods due to its greater sensitivity, specificity, accuracy, and reproducibility. In this study, a duplex ddPCR assay for the detection of BCC and S. maltophilia in BSIs was developed.